A kind of synthetic method of styrenated phenol

Through the method of supporting composite solid acid catalyst and step-by-step dropwise addition of styrene, the problem of excessive phenol residue and acidic catalyst content in styrene phenol production is solved, and a high purity and high yield product is achieved, suitable for electronics Chemical application.

CN118084625BActive Publication Date: 2024-12-27ZHEJIANG HUANGMA TECH CO LTD +3
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410090379.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-01-23
Publication Date
2024-12-27
Estimated Expiration
2044-01-23

AI Technical Summary

Technical Problem

In the existing production process of styrene phenol, there are problems with phenol residues, by-product polystyrene and acidic catalysts, which leads to poor product quality and difficult to meet the application requirements of electronic chemicals.

Method used

The supported composite solid acid catalyst is used to react by adding styrene in step by step, and after cooling, it is subjected to suction filtration and heat-raising distillation to avoid the autopolytic styrene and acidic catalyst residue.

Benefits of technology

The complete reaction of phenol is achieved, which reduces the self-polytic styrene and acidic catalyst residues, improves the purity and yield of the product, and is suitable for high-demand applications such as photoresist developer.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004676514640000081
    Figure BDA0004676514640000081
  • Figure BDA0004676514640000121
    Figure BDA0004676514640000121
  • Figure BDA0004676514640000131
    Figure BDA0004676514640000131
Patent Text Reader

Abstract

The present invention provides a method for synthesizing styrenated phenol, comprising the following steps: S1, metering preheated phenol into a reactor, purging nitrogen, heating to 60-80°C, adding a supported composite solid acid catalyst, purging nitrogen, stirring evenly, reaching and maintaining the reaction temperature, dropping part of styrene, stopping the dropping and stirring until the reaction system is uniform and stable, and then dropping the remaining part of styrene; S2, after the dropping is completed, heating to 90-130°C, keeping the temperature for 30-120 minutes; S3, after the reaction is completed, cooling to below 60°C, suction filtering, heating and distilling to obtain the product styrenated phenol. The present invention can solve the problems of residual raw material phenol, excessive content of by-product polystyrene and acid catalyst in traditional processes.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of fine chemical preparation, and particularly relates to a method for synthesizing styrenated phenol under the action of a supported composite solid acid catalyst. Background Art

[0002] Styrenated phenol is a product obtained by alkylation reaction of styrene and phenol under the action of a catalyst. Styrenated phenol has many uses, and can be used as an environmentally friendly rubber antioxidant or as an alkylphenol antioxidant, and its dosage is very large. At the same time, styrenated phenol can be further reacted with ethylene oxide and propylene oxide to obtain styrenated phenol polyether, which is also an important raw material with excellent emulsification, temperature viscosity and bactericidal properties, low volatility and stable performance. It is an important component of pesticides, coatings and cleaning agents, especially in electronic chemicals such as color filters, liquid crystal panels of thin film transistors and photoresist developers, with an annual demand of more than 10,000 tons and increasing day by day.

[0003] At present, the traditional production process of styrenated phenol at home and abroad has the following problems: the liquid acid catalyst used is difficult to remove and corrosive to equipment, the effective content of binary substitution is low, the phenol residue is high, and it contains large molecular weight polystyrene polymers.

[0004] Specifically, the catalysts used in the current preparation process are generally acidic catalysts such as hydrochloric acid, sulfuric acid, phosphoric acid, oxalic acid, p-toluenesulfonic acid and composite acids, which are characterized by high activity and low cost, but are prone to incomplete reaction and phenol residue. They are also corrosive to equipment, especially hydrochloric acid and sulfuric acid, which are more corrosive and require special equipment. In addition, liquid catalysts are difficult to separate from the product, and residues in the product affect downstream applications. On the other hand, the reaction is carried out under high temperature conditions, styrene is prone to self-polymerization, and the styrene self-polymer reacts with phenol for alkylation. The by-products obtained must be removed and filtered with an adsorbent, and the production process is cumbersome, which increases costs.

[0005] The alkylation reaction of phenol and styrene will produce polystyrene polymers and phenol residues, resulting in the presence of polystyrenated phenol polyethers and phenol polyethers in the synthesized polyether. Due to its large spatial structure, polystyrenated phenol polyethers are easy to block the filter membrane during the preparation of developer filtration, affecting the filtration process. If they are mixed in the developer, they will affect the development effect. Small molecular phenol polyethers are interspersed between styrenated phenol polyoxyethylene ethers, which increases the surface strength of the liquid film, thereby increasing the stability of the foam, which is not conducive to defoaming. In addition, the alkylation reaction usually uses liquid acid as a catalyst, and the liquid acid catalyst often remains in the product and is difficult to remove. It will form salts with the alkaline substances in the developer formula, directly affecting the effect of the developer. Therefore, it is difficult to meet the requirements when styrenated phenol polyoxyethylene ethers produced by traditional process methods are used in electronic chemicals, especially in photoresist developers.

[0006] To solve the above problems, Chinese patent CN107253902A discloses a method for synthesizing styrenated phenol in a microreactor using an organic acid as a catalyst. The method using a microreactor can effectively control the violent exothermic reaction and reduce the generation of phenol residues and polystyrenated phenol byproducts; Patent CN110981701A is optimized on this basis, using multiple microreactors, adding styrene in steps to react, improving the yield, and reducing the generation of byproducts such as styrene self-polymers. However, this method also uses organic acids such as p-toluenesulfonic acid as catalysts, and ages in a delay tube and an aging kettle. It also has the same shortcomings as the kettle reactor, and the acid dosage is large and difficult to remove. The cost of using microreactor equipment is high, the operation is difficult, and it is difficult to industrialize in large quantities.

[0007] In order to solve the problems of equipment corrosion and acid removal difficulties, people began to explore the use of heterogeneous solid catalysts. Patent CN103880603A discloses a method for catalytic preparation of styrenated phenol, using macroporous strong acid cation exchange resin as a catalyst. Due to its high catalytic activity and low reaction temperature, it overcomes the shortcomings of the existing styrenated phenol synthesis process, such as more styrene self-polymers, dark color and acid removal difficulties. However, the process catalyst has poor thermal stability, low selectivity of product components, and more impurities, making it difficult to achieve industrial production. Summary of the invention

[0008] The object of the present invention is to provide a novel method for synthesizing styrenated phenol, which can solve the problems of residual raw material phenol, excessive content of by-product polystyrene and acid catalyst, etc.

[0009] The technical solution of the present invention to solve the above technical problems is as follows:

[0010] A method for synthesizing styrenated phenol, characterized in that it comprises the following steps:

[0011] S1. Measure the preheated phenol and put it into the reactor, purge nitrogen, heat it to 60-80°C, put in the supported composite solid acid catalyst, purge nitrogen, stir evenly, reach and maintain the reaction temperature, add part of styrene dropwise, stop adding dropwise and stir until the reaction system is uniform and stable, and then add the remaining part of styrene dropwise;

[0012] S2. After the addition is completed, the temperature is raised to 90-130°C and kept warm for 30-120 minutes;

[0013] S3. After the reaction is completed, the temperature is lowered to below 60°C, filtered, and heated for distillation to obtain the product styrenated phenol.

[0014] One implementation method is:

[0015] S1. Measure the preheated phenol and put it into the reactor, purge nitrogen, heat it to 75°C, put in the supported composite solid acid catalyst, purge nitrogen, stir evenly, reach and maintain the reaction temperature, add part of styrene, stop dropping, stir for 20 minutes, and then add the remaining part of styrene; the speed of the stirring device is 200-300r / min;

[0016] S2. After the addition is completed, the system is heated to 90-130°C and kept warm for 30-120 minutes;

[0017] S3. After the reaction is completed, the temperature is lowered, suction filtered, and the temperature is raised for distillation to obtain the product styrenated phenol.

[0018] The phenol and styrene in the preparation process can be industrial grade raw materials.

[0019] Preferably, in S1, the amount of raw materials is: styrene (molar number): phenol (molar number) = 0.8 to 3.2:1, more preferably 1.8 to 2.2:1.

[0020] In the above S1, the amount of the supported composite solid acid catalyst is 1-10% of the weight of the phenol feed, and more preferably 3-6%.

[0021] In S1, the amount of styrene added dropwise for the first time is 1 / 10 to 1 of the total amount, excluding 1; more preferably 3 / 10 to 7 / 10; and more preferably 3.5 / 10 to 5.5 / 10.

[0022] In S1, the reaction temperature of the dropwise addition of styrene is 75 to 120° C., more preferably 80 to 95° C. The total time of the dropwise addition of styrene is controlled to be 60 to 200 min, more preferably 90 to 180 min.

[0023] In the S2, the insulation temperature is 90-130°C, more preferably 95-110°C, and more preferably 96-99°C; the insulation time is 30-150 min, more preferably 50-130 min; and more preferably 60-120 min.

[0024] The preparation method of the supported composite solid acid catalyst described in S1 is as follows:

[0025] M1, fully dissolving a certain amount of nano-scale silicon dioxide in a mixed solvent A consisting of water, ethanol and hydrochloric acid, removing insoluble solid particles by solid-liquid separation, and preparing a mixed solution A1;

[0026] M2, dissolving a certain amount of perfluorosulfonic acid resin in a mixed solvent B consisting of water, ethanol and isopropanol to prepare a mixed solution B1;

[0027] M3. Then, solutions A1 and B1 are mixed and stirred. After stirring evenly, a certain amount of p-toluenesulfonic acid is added, and the mixture is mixed and stirred evenly again, and then the solvent is removed; finally, the mixture is washed with water and acidified to obtain a supported composite solid acid catalyst.

[0028] The amount of the nano-scale silicon dioxide added in the M1 is 10% to 50% of the mixed solvent A, preferably 20% to 40%.

[0029] The mass percentage content of ethanol in the mixed solvent A in M1 is 0-60%, excluding 0, and the mass percentage content of hydrochloric acid is 1%-25%. Preferably, the mass percentage content of ethanol is 20%-40%, and the mass percentage content of hydrochloric acid is 5%-15%.

[0030] In the M2, the amount of the added perfluorosulfonic acid resin accounts for 5% to 40% of the weight of the mixed solvent B, preferably 8% to 30%.

[0031] In the step M2, the ethanol content in the mixed solvent B is 1% to 30%, and the isopropanol content is 1% to 50%; preferably, the ethanol content is 10% to 20%, and the isopropanol content is 10% to 30%.

[0032] In the preparation process of the supported composite solid acid catalyst, the ethanol, hydrochloric acid and isopropanol are all ideal pure substances and can be prepared with solutions of appropriate concentrations.

[0033] In the M3, the mass ratio of the added p-toluenesulfonic acid to the perfluorosulfonic acid resin is 1:1-10, and more preferably 1:3-8.

[0034] In the M3, the acidification process is: acidification with 1-3 mol / L hydrochloric acid for 1-5 hours.

[0035] In the M3, after the acidification process, the following steps are further included: vacuuming and heating at 50-70°C, and when the temperature reaches 110-130°C, keeping the temperature and vacuum for 18-30 hours.

[0036] More specifically, the preparation method of the supported composite solid acid catalyst described in S1 is as follows:

[0037] M1, fully dissolving a certain amount of nano-scale silicon dioxide in a mixed solvent A consisting of water, ethanol and hydrochloric acid, and removing insoluble solid particles by centrifugation at 2500-3500 rpm to obtain a mixed solution A1;

[0038] M2, dissolving a certain amount of perfluorosulfonic acid resin in a mixed solvent B consisting of water, ethanol and isopropanol to prepare a mixed solution B1;

[0039] M3. Then, the solutions A1 and B1 are mixed and stirred. After stirring evenly, a certain amount of p-toluenesulfonic acid is added, and the mixture is mixed and stirred evenly again. Then, the mixture is heated in a water bath and evaporated to remove the solvent. After washing with water, the mixture is acidified with 1-3 mol / L hydrochloric acid for 1-5 hours. At 50-70°C, the mixture is vacuumized while the temperature is increased. When the temperature reaches 110-130°C, the mixture is kept warm and vacuumized for 18-30 hours. After cooling, the supported composite solid acid catalyst can be obtained.

[0040] Compared with the prior art, the present invention has the following beneficial effects:

[0041] The invention uses phenol and styrene as raw materials, adopts a supported composite solid acid as a catalyst, and reacts by dropwise adding styrene in steps. After the reaction is complete, the product is obtained by cooling, filtering, and heating, and distilling.

[0042] The step-by-step dripping method can be used to react phenol completely to the greatest extent possible and prevent the self-polymerization of styrene. The use of solid catalysts is easy to filter and separate, and no neutralization, refining and other processes are required. The product performance will not be affected by the residual catalyst, and the reaction equipment will not be corroded, and there is no "three wastes" pollution; perfluorosulfonic acid resin has super acidity, high catalytic activity, and low reaction temperature, thereby avoiding the possibility of styrene self-polymerization at high temperature, and the reaction is thorough, thereby reducing phenol residues. At the same time, perfluorosulfonic acid resin has strong heat resistance and is a catalyst with strong stability; the specific surface area of ​​the perfluorosulfonic acid resin after loading is greatly increased, and the acidic site is easily contacted by the reactants, overcoming The problem that ordinary perfluorosulfonic acid resin has no pore structure, and its incomparable surface area and pore volume make it impossible for the reactant molecules to contact with the active groups, thus failing to exert the super acid performance of perfluorosulfonic acid, is solved. By loading porous materials, its catalytic activity is enhanced and its service life is extended; composite p-toluenesulfonic acid, p-toluenesulfonic acid has good compatibility with phenol and styrene, has high activity in their alkylation reactions, and has no carbonization effect. Secondly, p-toluenesulfonic acid has the effect of strengthening acidity, which is beneficial to enhancing the acidity of perfluorosulfonic acid and making up for the disadvantage of weakened catalytic activity of perfluorosulfonic acid resin in the later stage.

[0043] Compared with the traditional liquid acid, the supported composite solid acid is used as the catalyst, which is easy to separate from the liquid phase reaction system, has high catalytic activity, thorough reaction, light color, high product purity, and does not corrode the reaction equipment. In particular, the catalytic synthesis of styrenated phenol has basically no phenol raw material and catalyst residue, no polystyrenated phenol by-products, high yield, low color, and high product quality. It is used as a starter to prepare the downstream product styrenated phenol polyether through ethoxylation reaction, without complicated post-processing procedures, and can meet the requirements of special polyethers used in photoresist developers. DETAILED DESCRIPTION

[0044] The present invention is further described below by way of examples. It should be noted that, without departing from the subject matter and spirit of the present invention, those skilled in the art may modify and change the specific embodiments, and are by no means limited to these examples. These modifications and changes also fall within the scope of the present invention. The scheme and effects of the present invention are further illustrated below in conjunction with catalyst preparation and synthesis examples.

[0045] Preparation of supported composite solid acid catalyst:

[0046] Catalyst 1:

[0047] M1. Dissolve 30 g of nano-scale silicon dioxide in 100 g of solvent A, wherein the composition of solvent A is 60 g of water, 30 g of ethanol (30% by mass concentration) and 10 g of hydrochloric acid (10% by mass concentration). After sufficient stirring and dissolving, centrifuge at 3000 rpm to remove insoluble solid particles;

[0048] M2, dissolving 15 g of perfluorosulfonic acid resin in a mixed solvent B consisting of 65 g of water, 15 g of ethanol (mass percent concentration of 15%) and 20 g of isopropanol (mass percent concentration of 20%);

[0049] M3. Then the two solutions obtained in steps M1 and M2 are mixed and stirred. After stirring evenly, 3 g of p-toluenesulfonic acid is added, and the mixture is mixed and stirred evenly again. Then, the mixture is heated in a water bath and evaporated to remove the solvent while stirring. Then, the mixture is washed with water twice, acidified with 2 mol / L hydrochloric acid for 3 hours, and then the mixture is heated at 60°C while being vacuumized. When the temperature reaches 120°C, the mixture is kept warm and vacuumized for 24 hours. After cooling, the supported composite solid acid catalyst 1 can be obtained.

[0050] Table 1. Preparation of supported composite solid acid catalysts by different combined preparation methods

[0051]

[0052] Combined with the catalysts prepared by different combination preparation methods in Table 1 above, the scheme and effect of the styrenated phenol preparation process route are further explained.

[0053] Embodiment 1:

[0054] 94 g of preheated phenol solution was put into a reactor, purged with nitrogen, stirred and heated, and the speed was controlled within 200-300 r / min. When the temperature reached 75°C, 3.76 g (4%) of supported composite catalyst 1 was added, purged with nitrogen, stirred evenly, and 131 g of styrene (6 / 10) was evenly added dropwise. The reaction temperature was controlled at 88-92°C. After stirring for 20 min, the remaining 87.4 g of styrene was added dropwise. The entire dropping process was maintained for about 100 min. After the dropping was completed, the temperature was raised to 92-96°C for insulation reflux reaction for 120 min. After cooling, filtration, catalyst recovery, and distillation at a higher temperature to remove impurities, styrenated phenol was obtained.

[0055] Embodiment 2:

[0056] The method of Example 1 was adopted, and the ratio of the stepwise addition of styrene was changed. The amount of styrene added for the first time was 65.52 g, and the amount added for the second time was 152.88 g. The molar ratio of styrene to phenol remained unchanged at 2.1:1, and other conditions remained unchanged.

[0057] Embodiment 3:

[0058] The method of Example 1 was adopted, the molar ratio of styrene to phenol was changed to 3.1:1, the dropping ratio of styrene remained unchanged, the amount of styrene added for the first time was 193.4 g, the amount added for the second time was 129 g, and other conditions remained unchanged.

[0059] Embodiment 4:

[0060] The method of Example 1 was adopted, except that the addition amount of the supported composite solid acid catalyst 1 was changed to 9.4 g, and other conditions remained unchanged.

[0061] Embodiment 5:

[0062] The method of Example 1 was adopted, except that the supported composite catalyst 2 was added, and other conditions remained unchanged.

[0063] Embodiment 6:

[0064] The method of Example 1 was adopted, except that the supported composite solid acid catalyst 5 was added, the added amount of the supported composite solid acid was 2 g, and other conditions remained unchanged.

[0065] Embodiment 7:

[0066] The method of Example 1 was adopted, except that the reaction temperature during the dropwise addition of styrene was changed to 116-120° C., and the other conditions remained unchanged.

[0067] Embodiment 8:

[0068] The method of Example 1 was adopted, and the insulation temperature was changed to 100-104° C., while other conditions remained unchanged.

[0069] Embodiment 9:

[0070] The method of Example 1 was adopted, except that the total time of the styrene addition process was changed to 170 min, and other conditions remained unchanged.

[0071] Embodiment 10:

[0072] The method of Example 1 was adopted, except that the holding time was changed to 40 min, and other conditions remained unchanged.

[0073] Embodiment 11:

[0074] The method of Example 1 was adopted, except that the supported composite solid acid catalyst 8 was added, the molar ratio of styrene to phenol was changed to 1.8:1, the reaction temperature during the styrene addition process was 82-86° C., and other conditions remained unchanged.

[0075] Embodiment 12:

[0076] The method of Example 1 was adopted, except that the supported composite solid acid catalyst 10 was added. The reaction temperature during the styrene addition process was 76-82° C., the addition time was 140 min, and other conditions remained unchanged.

[0077] Embodiment 13:

[0078] The method of Example 1 was adopted, except that the addition amount of the supported composite solid acid catalyst 1 was changed to 5.8 g, and other conditions remained unchanged.

[0079] Embodiment 14:

[0080] The method of Example 1 was adopted, the molar ratio of styrene to phenol was changed to 1.1:1, the insulation temperature was 120-125° C., the insulation time was 150 min, and other conditions remained unchanged.

[0081] Comparative Example 1:

[0082] Put 94g of preheated phenol solution into the reactor, purge with nitrogen, start stirring and heating, control the speed within 200-300r / min, add 3.76g of p-toluenesulfonic acid catalyst when the temperature rises to 75℃, purge with nitrogen, stir evenly, evenly add 131g of styrene, control the reaction temperature at 88-92℃, stir for 20min, add the remaining 87.4g of styrene, and keep the whole adding process for about 100min. After the addition is completed, heat to 92-96℃ and keep reflux reaction for 120min. After removing impurities by vacuum distillation, styrenated phenol is obtained.

[0083] Comparative Example 2:

[0084] Put 94g of preheated phenol solution into the reactor, purge with nitrogen, start stirring and heating, control the speed within 200-300r / min, add 3.76g of sulfuric acid (mass concentration is 50%) when the temperature rises to 75℃, purge with nitrogen, stir evenly, and then evenly add 131g of styrene. The reaction temperature is controlled at 88-92℃, and after stirring for 20min, add the remaining 87.4g of styrene. The whole dropping process is maintained for about 100min. After the dropping is completed, heat to 92-96℃ and keep warm for reflux reaction for 120min. After removing impurities by vacuum distillation, styrenated phenol is obtained.

[0085] Comparative Example 3

[0086] 94 g of preheated phenol solution was added to the reactor, purged with nitrogen, and stirring and heating were started. The speed was controlled within 200-300 r / min. When the temperature rose to 75°C, 1.175 g of perfluorosulfonic acid resin and 0.235 g of p-toluenesulfonic acid were added. Nitrogen was purged and stirred evenly. Then 131 g of styrene (6 / 10) was evenly added dropwise. The reaction temperature was controlled at 88-92°C. After stirring for 20 minutes, the remaining 87.4 g of styrene was added dropwise. The whole dropping process was maintained for about 100 minutes. After the dropping was completed, the temperature was raised to 92-96°C for insulation and reflux reaction for 120 minutes. After cooling and suction filtration to remove the filter residue, the impurities were removed by distillation at a higher temperature to obtain styrenated phenol.

[0087] The components of the products obtained in each embodiment and comparative example were analyzed by high performance liquid chromatography to analyze the yield, distyrenated phenol content, polymer impurities, and phenol residue.

[0088] Table 2 Comparison of liquid phase analysis components of each embodiment and comparative example sample

[0089]

[0090]

[0091] As can be seen from Table 2, the yields of Example 1 and Example 9 and the productivity of diphenylethylene phenol are very high, there is no phenol residue, the polymer impurities are less than 100ppm, and the impact on product performance is negligible, which is significantly better than the comparative example and other embodiments, and belongs to a better solution. The yields of Examples 1 to 13 and the productivity of diphenylethylene phenol are significantly higher than those of Comparative Examples 1, 2 and 3, and the contents of phenol residue and polymer impurities are significantly less than those of Comparative Examples 1, 2 and 3, indicating that the supported solid catalyst and catalytic synthesis method manufactured by the present invention are significantly better than the existing synthetic catalytic synthesis method.

[0092] It can also be seen from Table 2 that, compared with Examples 1 and 13, more catalyst is added in Example 4, and the polymer impurities are significantly increased. The reason is that more catalyst is added, which significantly reduces the activation energy of the reaction and increases the reaction rate. Similarly, the self-polymerization rate of styrene also increases rapidly. The added styrene undergoes self-polymerization without completely reacting with phenol, resulting in more polymers.

Claims

1. A method for synthesizing styrenated phenol, characterized in that: The following steps are involved: S1. Measure the preheated phenol and put it into the reactor, purge nitrogen, heat it to 60-80°C, put in the supported composite solid acid catalyst, purge nitrogen, stir evenly, reach and maintain the reaction temperature, add part of styrene dropwise, stop adding dropwise and stir until the reaction system is uniform and stable, and then add the remaining part of styrene dropwise; S2. After the addition is completed, the temperature is raised to 90-130°C and kept warm for 30-120 minutes; S3, after the reaction is completed, the temperature is lowered to below 60°C, filtered, heated and distilled to obtain the product styrenated phenol; In S1, the amount of the supported composite solid acid catalyst is 1 to 10% of the weight of the phenol feed; The preparation method of the supported composite solid acid catalyst is as follows: M1, fully dissolving silicon dioxide in a mixed solvent A consisting of water, ethanol and hydrochloric acid to prepare solution A1, and removing insoluble solid particles by solid-liquid separation; M2, dissolving perfluorosulfonic acid resin in a mixed solvent B consisting of water, ethanol and isopropanol to prepare a solution B1; M3, then the solution A1 and B1 are mixed, stirred evenly, p-toluenesulfonic acid is added, mixed and stirred evenly again, and then the solvent is removed; finally, washed with water and acidified to obtain a supported composite solid acid catalyst; The silicon dioxide is nano-scale silicon dioxide, and its addition amount is 10% to 50% of the mass of the mixed solvent A; The content of ethanol in the mixed solvent A in the M1 is 0-60%, excluding 0, and the content of hydrochloric acid is 1%-25%; in the M3, the mass ratio of the added p-toluenesulfonic acid to the perfluorosulfonic acid resin is 1:1-10; In the M2, the amount of the added perfluorosulfonic acid resin accounts for 5% to 40% of the mass of the mixed solvent B; the content of ethanol in the mixed solvent B in the M2 is 0 to 30%, excluding 0, and the content of isopropanol is 0 to 50%, excluding 0.

2. The synthesis method according to claim 1, characterized in that: In the S1, the molar ratio of styrene to phenol is 0.8 to 3.2:

1.

3. The synthesis method according to claim 1, characterized in that: In the above S1, the amount of the supported composite solid acid catalyst is 3% to 6% of the weight of the phenol feed.

4. The synthesis method according to claim 1, characterized in that: In S1, the amount of styrene added dropwise for the first time is 1 / 10 to 1 of the total amount of styrene, excluding 1.

5. The synthesis method according to claim 4, characterized in that: In S1, the amount of styrene added dropwise for the first time is 3 / 10 to 7 / 10 of the total amount of styrene.

6. The synthesis method according to claim 1, characterized in that: In S1, the reaction temperature is 75-120° C. when the dropwise addition of styrene is started, and the total time for the dropwise addition of styrene is controlled to be 60-180 min.

7. The synthesis method according to claim 1, characterized in that: In S2, the insulation temperature is 90-130° C., and the insulation time is 30-120 min.